PECULIARITIES OF IMMUNITY IN PATIENTS WITH DIABETES MELLITUS AND CHRONIC PYELONEPHRITIS - Busygina, Yu.; Driyanska, V.; Stepanova, N.; Gaysenyuk, F.; Lebed, L.; Lavrenchuk, O.; KolesnyкM. (Ukrainian Journal of Nephrology and Dialysis, 2017)
The pro- and antiinflammatory cytokines participate in antiinfective immunity, that is why it is necessary study their peculiarities in determination of the role in the immunopathogenesis of pyelonephritis, including complications of diabetes mellitus (DM). The purpose of the work is to study the immune status and levels of pro- and antiinflammatory blood cytokines in the patients with chronic pyelonephritis (CPN), to determine the peculiarities in cases of DM. Materials and methods. The immuno-enzymic method ELISA and the corresponding test-systems were used to study the levels of cytokines in blood and also standard immunity indices. Results. The analysis showed the significant increase in levels of all studied pro- (TNF-б, MCP-1, IL-17, -23) and antiinflammatory (IL-4, TGF-в) cytokines in all patients with CPN and in every group – with (2) and without DM (3). In 3 gr. (CPN+DM) the CD4+/CD8+ are significantly lower, while in IgM, МСР-1 and TNF-б levels – higher than in the 1 gr. (DM without CPN), and IL-4 , NGAL – than in 2 gr. (CPN without DM). Conclusion. The high level of cytokines (TNF-б, MCP-1 and IL-23) in blood confirms their important role in CPN+DM and CPN without DM. In patients with CPN+DM marked reduction in regulatory index (CD4+/CD8+) and higher levels of proinflammatory cytokines (TNF-б, MCP-1). Our investigation showed that NGAL level in serum was increased more significantly in 3 gr.; this fact may confirm that renal disfunction was more severe in patients with CPN+DM.